State of the art procedures towards reactive [18F]fluoride in PET tracer synthesis - Lizeth Y. F. Haveman; Danielle J. Vugts; Albert D. Windhorst (SpringerOpen, 2023)
Abstract Background Positron emission tomography (PET) is a powerful, non-invasive preclinical and clinical nuclear imaging technique used in disease diagnosis and therapy assessment. Fluorine-18 is the predominant radionuclide used for PET tracer synthesis. An impressive variety of new 'late-stage' radiolabeling methodologies for the preparation of 18F-labeled tracers has appeared in order to improve the efficiency of the labeling reaction. Main body Despite these developments, one outstanding challenge into the early key steps of the process remains: the preparation of reactive [18F]fluoride from oxygen-18 enriched water ([18O]H2O). In the last decade, significant changes into the trapping, elution and drying stages have been introduced. This review provides an overview of the strategies and recent developments in the production of reactive [18F]fluoride and its use for radiolabeling. Conclusion Improved, modified or even completely new fluorine-18 work-up procedures have been developed in the last decade with widespread use in base-sensitive nucleophilic 18F-fluorination reactions. The many promising developments may lead to a few standardized drying methodologies for the routine production of a broad scale of PET tracers.